Penyelesaian Sengketa Pembatalan Merek Pada Kelas Berbeda Melalui Pengadilan Negeri (Studi Putusan Nomor: 3011 K/Pdt/2018) - Kefara Gustinia Digmadani; Ayu Citra Santyaningtyas (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2022)
ABSTRACT: This case began when Andri Anis and Yasmar registered the Soerabi Enhaii brand in class 43, namely restaurants. This makes Cecep Sumarno as the owner of the same trademark in class 30 feel disadvantaged due to registration in bad faith by Andri Anis and Yasmar. Therefore Cecep Sumarno sued to the District Court with a lawsuit against the law. Then, Cecep Sumarno submitted an application to the Supreme Court with the principal request being to cancel Andri Anis and Yasmar's trademarks. Andri Anis and Yasmar's actions violate Article 21 verse 3 of Mark and Geographical Indication Law, that “trademark will be rejected if the mark is submitted by an applicant who registers the mark in bad faith”. The researcher aims to examine the reasons for the cancellation of the mark, the legal consequences of registering the same mark, as well as the legal considerations of the judge who rejected Cecep Sumarno's appeal. The research method used is a normative juridical research method using a statutory approach and a conceptual approach. The reason for the cancellation of the mark proposed by Cecep Sumarno is that the cancellation of the registration mark has bad intentions. The legal consequence of trademark equality is that Cecep Sumarno as the owner of the mark in class 30 can file a lawsuit for the cancellation of Andri Anis and Yasmar's trademark in class 43 through the Commercial Court. The judge's legal considerations in the Decision of the Supreme Court of the Republic of Indonesia Number: 3011 K/Pdt/2018 that based on the judex facti of the DKI Jakarta High Court does not conflict with the law. The trademark dispute filed by Cecep Sumarno basically asks for the cancellation of the mark which is not the authority of the District Court. KEYWORDS: Mark Revocation, Mark Similarity, Dispute Settlement